The Educational Value of the Miracles of the Qur’an in the Curriculum and Learning Outputs in the Digital Literacy Era - Abd Hamid; Abd. Kahar (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This article discusses the Design of curriculum development and educational outputs based on the miracles of the Qur’an. In this study, the author uses descriptive-critical research, with greater emphasis on the strength of the analysis of existing sources and data, drawing on existing theories and concepts to interpret the writings that lead to the discussion. Based on the results of the primary source study, it can be concluded that the educational approach that makes the Qur’an and As-Sunnah the primary foundation in the entire learning process includes aspects of faith, worship, morals, and science. The focus is to form a generation of Qur’anic scholars who are intellectually intelligent, have noble characters (morals), and can read, memorize, understand, and practice the contents of the Qur’an in everyday life. The output of the Qur’an-based curriculum generally aims to form Insan Kamil who integrate spiritual, intellectual, and moral aspects. Keywords: Educational Values, Miracles of the Qur’an, Curriculum, Learning